Penilaian Likelihood Risiko Fraud Dalam Manajemen Pemerintahan - Mustofa Kamal (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2018)
This study aims to determine the likelihood level of fraud risk in the planning, organizing, actuating, controlling (POAC) aspects of government agencies and gives an example of fraud risk ranking list. Qualitative research method used with survey technique to 83 respondents of training participants in education center and supervision training of BPKP. Respondents rated likelihood on fraud risk in the POAC aspect. The results show that 8 fraud risks in POA with likelihood levels are frequent/often occurring and 31 fraud risks in POAC with likelihood levels have occurred. This suggests there is an increase in the likelihood of POA fraud risk, often occurring, from previous studies (BPKP, 2004), have occurred.